Aqueous solution blending route for preparing flexible and antistatic polyimide/carbon nanotube composite films with core‐shell structured polyimide/graphene microspheres. Issue 9 (19th July 2022) - Jiang, Hanzhou; Xu, Lubo; Chen, Guofei; Fang, Xingzhong
Abstract: To explore the process of preparing polyimide (PI) microspheres with specific particle size, the effects such as the ratio of surfactant to PI, concentration of PI, stirring speed, and temperature on the particle size and distribution of PI microspheres were investigated in detail. The core‐shell structured PI@reduced graphene oxide (rGO) microspheres were prepared by reduction of PI microspheres with an average particle size of 1.11 μm coated with GO. The PI/carbon nanotube (CNT) composites films were fabricated with poly(amic acid) ammonium salts (PAAS) aqueous solution blending route. A three‐dimensional (3D) conductive network was constructed due to the CNTs were connected by microspheres and arranged in a random orientation. Thus, The PI/CNT composite films exhibited well antistatic properties and volume resistivity dropped by five orders of magnitude to 6.56 × 10 5  Ω·cm after adding 15 phr PI@rGO microspheres. Moreover, the composite films still have good mechanical properties and excellent thermal properties. Abstract :